تعارض المصالح المرسلة مع خبر الواحد عند الإمام مالك دراسة وتحقيق - جلة, مصطفى (جامعة الوادي - University of Eloued, 2022)
ملخص: قد اشتهر عند المتأخرين من أهل العلم أن من أصول الإمام مالك تقديم المصلحة على خبر الآحاد متى تعارضا ولم يمكن الجمع بينهما, ومعلوم أن مرتبة المصلحة في الاحتجاج متأخرة عن مرتبة السنة فكيف ساغ لإمام دار الهجرة أن يقدمها على الخبر؟ وقد جاء هذا البحث للوقوف على مدى صحّة هذه الدعوى دراسة وتحقيقا, مع ذكر بعض النماذج التي تكشف لنا حقيقة مذهب الإمام مالك في هذه المسألة. وقد توصلنا من خلال هذه الدراسة إلى أن المصلحة إذا كانت ثابتة ثبوتا قطعيا, وكانت من جنس المصالح التي أقرتها الشريعة وملائمة لها, فإنها تُخصص النص عند مالك إذا كان عاما غير قطعي, وترد الآحاد إن عارضها. Abstract : It is well known to the late scholars that one of the origins of Imam Malik is to provide interest on the news of Sundays when they are opposed and cannot be combined, and it is known that the rank of interest in protest is late in the year, so how can i ask the imam of Dar al-Immigration to present it on the news? This research has come to determine the validity of this study and investigation, with some examples that reveal to us the truth of Imam Malik's doctrine in this matter. We have concluded through this study that if the interest is firmly established and is of the sex of the interests approved by the Shariah and appropriate to it, it allocates the text to the owner if it is a non-definitive year, and the ones are given if opposed to it.
مقال
Keywords: الإمام مالك؛ التعارض ؛ الأحاديث؛ المصلحة؛ خبر الواحد.; Imam Malik; Conflict; Hadiths; interest ; One news